Glutamatergic transmission in the avian brain: model for human excitotoxicity disorders Study - M.R., Islam; Y., Atoji; J.M., Abdullah (Universiti Kebangsaan Malaysia, 2013)
Glutamatergic dysfunction has been suggested as a possible substrate of the pathophysiology of many neurodegenerative diseases, specifically since glutamatergic transmission is severely altered by the early degeneration of cortico-cortical connections and hippocampal projections in Alzheimer’s disease, schizophrenia and Huntington’s disease in humans. Of the multiple genes, vesicular glutamate transporters, glutamate receptors and excitatory amino acid transporters have a significant role in glutamatergic transmissions. The regional differences of glutamatergic neurons and glutamate receptor neurons suggest many glutamatergic projections in the avian brain. Glutamatergic target areas are expected to show high activity of glutamate transporters that remove the released glutamate from the synaptic clefts. The distribution of the glutamate-related genes indicates that many glutamatergic transmissions exist in the avian brain. This review provide insights of glutamatergic circuits in birds particularly in the pallial organization of glutamatergic neurons and connection with the striatum and hippocampal-septal pathway and comparison with those of mammalian brain which are responsible for Alzheimer’s disease, schizophrenia and Huntington’s disease in humans.